Hippocratea africana Ethanol Root Extract and Fractions Attenuate Doxorubicin-Induced Testicular Toxicity and Oxidative Stress - Noah, Kufre U; Okokon, Jude E (Biology, Medicine, & Natural Product Chemistry, 2024)
Hippocratea africana root, used locally in treating poisoning, was investigated to confirm its antidotal potential in rats. The root extract (200-600 mg/kg) and fractions; dichloromethane (DCM) and aqueous, 400 mg/kg) were evaluated for hepatoprotective activity against doxorubicin-induced testicular toxicity in male rats. Testosterone level, lipid profile indices, testicular oxidative stress markers, and testis histology were used to assess the testicular protective effect of the extract. The root extract (200-600 mg/kg) and fractions, dichloromethane (DCM) and aqueous, 400 mg/kg reduced the serum levels of total cholesterol, triglycerides, LDL, and VLDL that were elevated by doxorubicin. In contrast, the high-density lipoprotein (HDL) reduced by doxorubicin was increased by the extract and fractions co-administration. Testosterone level, which was significantly (p<0.05) reduced by doxorubicin, was significantly (p<0.05-0.01) elevated by the root extract and fractions co-administration. The levels of GSH, GST, SOD, GPx, and CAT that were decreased by doxorubicin were significantly (p<0.01) elevated, and raised MDA level was reduced by the root extract and fractions. Histology of the testes sections of extract/fractions -treated animals showed absent/or reductions in the pathological features compared to the organotoxic-treated animals. The chemical pathological changes were consistent with histopathological observations, suggesting marked testicular protective potential. The anti-toxic effect of this plant may in part be mediated through the chemical constituents of the plant. The plant, H. africana possesses anti-toxicant properties which can be exploited in the treatment of doxorubicin-related toxicities.